European aid and health system strengthening: an analysis of donor approaches in the DRC, Ethiopia, Uganda, Mozambique and the global fund - Lies Steurs (Taylor & Francis Group, 2019)
Background: In the field of international health assistance (IHA), there is a growing consensus on the limits of disease-specific interventions and the need for more health system strengthening (HSS). European donors are considered to be strong supporters of HSS. Nevertheless, little is known about how their support for HSS translates into concrete policies at partner country level. Furthermore, as development cooperation is a shared policy between the EU and its Member States, it remains unclear to what extent European donors share a similar approach. Objective: This article reviews a PhD thesis on European aid and HSS. The thesis investigated (1) the approaches of European donors towards IHA, and (2) the extent to which there are similarities or differences between them. An original analytical framework was developed to make a fine-grained analysis of European donors' approaches in the DRC, Ethiopia, Uganda and Mozambique. In addition, the relation of European donors with the Global Fund was investigated. Methods: An abductive research approach was used during which literature review, data generation, analysis and research design mutually influenced each other. The research built on a wide range of empirical data, including semi-structured interviews with 123 respondents, policy documents and descriptive statistical analysis. Results and conclusion: Four 'types' of European donors were identified, which vary in their focus (issue-specific versus comprehensive) and their level of support to and involvement of recipient states. Despite this heterogeneity at a specific level, there is still a general degree of 'unity' among European donors, especially compared with the US. Yet, there are signs that the 'transatlantic' divide on HSS may be converging, as European donors tend to focus more explicitly on result-oriented approaches traditionally associated with the US and Global Health Initiatives. Consequently, European donors play a limited role in bringing HSS more to the forefront in IHA.